2014
DOI: 10.3319/tao.2014.05.19.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

Fault Orientation Determination for the 4 March 2008 Taoyuan Earthquake from Dense Near-Source Seismic Observations

Abstract: On 4 March 2008, a moderate earthquake (M L = 5.2) occurred in southern Taiwan and named as the Taoyuan earthquake, preceded by foreshocks and followed by numerous aftershocks. This earthquake sequence occurred during the TAIGER (TAiwan Integrated GEodynamics Research) controlled-source seismic experiment. Consequently, several seismic networks were deployed in the Taiwan area at this time and many stations recorded this earthquake sequence in the near-source region. We archived and processed near-source obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The coseismic slip models for 2008 Taoyuan, 2010 Jiashian, 2012 Wutai, and 2016 Meinong mainshocks were derived from Shih et al (), Lee et al (), Chiang et al (), and Huang et al (), respectively. The fault parameters corresponding to each of the mainshocks are listed in Table .…”
Section: Coulomb Stress Change Induced By Four Mainshocksmentioning
confidence: 99%
See 2 more Smart Citations
“…The coseismic slip models for 2008 Taoyuan, 2010 Jiashian, 2012 Wutai, and 2016 Meinong mainshocks were derived from Shih et al (), Lee et al (), Chiang et al (), and Huang et al (), respectively. The fault parameters corresponding to each of the mainshocks are listed in Table .…”
Section: Coulomb Stress Change Induced By Four Mainshocksmentioning
confidence: 99%
“…The uniform and oversimplified slip inferred using empirical relationships in the 2008 event may lead to a biased result and interpretation, while three other source models also have uncertainties that propagate through the Coulomb stress calculations (e.g., Parsons, ). In this study we did not test the stress computation using different source models, given the selected models themselves were compared with other results in the original papers (Chiang et al, ; Huang et al, ; Lee et al, ; Shih et al, ). Instead, we attempted to approach uncertainty produced by receiver fault orientations, as shown in Figures and .…”
Section: Uncertainties In Stress Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…The double-difference algorithm has been implemented in the computer program HypoDD (Waldhauser 2001). The program HypoDD has been extensively tested with data from permanent networks and aftershock arrays around the world to verify its ability to improve the image of seismicity (Rietbrock and Waldhauser 2004;Waldhauser et al 2012;Shih et al 2014). The earthquake data of P-wave arrival times collected from stations of the BMKG seismic network have been analyzed in this study based on the HypoDD algorithm.…”
Section: Relocation Of Bmkg Catalogue Eventsmentioning
confidence: 99%
“…From the aftershock spatial distribution, the major fault plane is ~10 km long along the strike and 10 km wide in the dip direction. Shih et al (2014) observed that relocated aftershocks formed clusters, and an area with low aftershock activity was beneath the mainshock. The aftershock distribution suggests a southeast-dipping fault plane, which is consistent with one of the nodal planes of the focal-plane solution for the mainshock.…”
Section: The Taoyuan Earthquake Of 4 March 2008mentioning
confidence: 99%